NUTRITIONAL INTERVENTION IN PRESCHOOL CHILDREN DIAGNOSED WITH OBESITY - Patrycja Wierzbowska; Hubert Kostka; Damian Dolata; Adrian Zagórski; Jadwiga Kleinrok; Anna Bereta-Kostaś; Rafał Kuśmider; Małgorzata Leśnik (International Journal of Innovative Technologies in Social Science, 2025)
Childhood obesity already affects ~8-9 % of 2 to 5 year‑olds and predicts later cardiometabolic disease. This review a) clarifies current diagnostic criteria for preschool obesity; b) maps key environmental and behavioral drivers; and c) assesses nutrition‑focused interventions delivered at family, preschool and policy levels.BMI for age still underpins WHO, CDC and IOTF charts; severe obesity cut offs and waist measures refine risk. Obesogenic pressures arise from energy‑dense home diets, fast food outlets, poor produce access and persuasive digital marketing. Roughly 40 RCTs show that high‑intensity (≥25 h) family programs pairing parental skill‑building with home food restructuring lower BMI‑z by up to -0.59 and maintain ≈ -0.20 after 2 y. Preschool curricula shave -0.10 to -0.12 BMI‑z across populations. Fiscal levers sugar‑sweetened‑beverage taxes, meal standards, front‑of‑pack warnings and advertising restrictions produce small but often equity‑enhancing shifts and act synergistically with micro‑environmental changes.Evidence favors early, layered action: precise growth surveillance, intensive family‑centered treatment, healthy preschool food policies and equity‑oriented regulation. Scaling integrated bundles with high fidelity and long follow‑up could curb the projected 42 % rise in early childhood obesity by 2035. Research needs include cost‑effectiveness of digital adjuncts, natural experiment tests of zoning and marketing reforms, and systems models quantifying interactive impacts of combined policy packages.